Autonomous and Intelligent Systems Second International Conference, AIS 2011, Burnaby, BC, Canada, June 22-24, 2011. Proceedings - Kamel, Mohamed; Karray, Fakhri; Gueaieb, Wail; Khamis, Alaa (Springer eBooks., 2011)
This book constitutes the refereed proceedings of the Second International Conference on Autonomous and Intelligent Systems, AIS 2011, held in Burnaby, BC, Canada, in June 2011, colocated with the International Conference on Image Analysis and Recognition, IACIAR 2011. The 40 revised full papers presented were carefully reviewed and selected from 62 submissions. The papers are organized in topical sections on autonomous and intelligent systems, intelligent and advanced control systems, intelligent sensing and data analysis, human-machine interaction, and intelligent circuit analysis and signal processing.